πScope: Python based scientific workbench with MDSplus data visualization tool - Shiraiwa, S.; Fredian, T.; Hillairet, J.; Stillerman, J. (Fusion engineering and design, 2016)
•πScope provides great enhancement in MDSplus data visualization.•πScope provides a single platform for both data browsing and complicated analysis.•πScope is scriptable and easily expandable due to its object oriented.•πScope is written in python and available from http://piscope.psfc.mit.edu/. A newly developed python based scientific data analysis and visualization tool, πScope (http://piscope.psfc.mit.edu), is reported. The primary motivation is 1) to provide an updated tool to browse the MDSplus data beyond existing dwscope/jScope and 2) to realize a universal foundation to construct interface tools to perform computer modeling from experimental data. To visualize MDSplus data, πScope has many features including overplotting different signals and discharges, generating various plot types (line, contour, image, etc.), performing in-panel data analysis using python scripts, and producing publication quality graphics. The logic to generate multi-panel plots is designed to be backward compatible with dwscope, enabling smooth migration for users. πScope uses multi-threading in data loading, and is easy to modify and expand due to its object-oriented design. Furthermore, A user can access the data structure both from a GUI and a script, enabling relatively complex data analysis workflow built quickly on πScope.